Snapshot of Accountability of Higher Education Governance - Rivai, Andi Muhammad; Nasriah, Nasriah; Akib, Haedar; Aliah, Nurul (Seminar Nasional LP2M UNM, 2024)
Governance accountability plays a crucial role in enhancing the quality, credibility, and competitiveness of higher education in an era marked by transparency and diverse public demands. This study is essential as it provides a comprehensive overview of higher education governance accountability, covering the management of resources, strategic decision-making, and the roles and responsibilities of stakeholders. The primary goal of the study is to analyze and explain governance accountability in higher education institutions. Using a descriptive-qualitative method with a constructive approach, data were collected through in-depth interviews, observations, and analysis of institutional documents. Universitas Negeri Makassar, a prominent university in Eastern Indonesia, was chosen as the locus due to its accreditation status and applied governance model. Thematic analysis was employed to identify key patterns related to governance accountability. The results revealed that although the university's nine faculties and postgraduate programs have implemented a well-structured governance system, challenges persist, such as limited information transparency due to leadership transitions, stakeholder representation issues, and difficulties in adopting digital-based performance evaluation mechanisms. These findings contribute to improving accountability systems in higher education and highlight the need for stronger transparency, responsiveness, internal audits, and capacity-building in institutional governance. Kata kunci: Accountability; Governance; Higher Education; Performance Evaluation